Pentingnya Pemasaran Jasa Pendidikan di Lembaga Pendidikan - Adawiah, Diah Robiatul; Abdul Muin; Anis Zohriah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The marketing function in educational institutions is to form a good image of the institution and attract the interest of a number of prospective students. This study aims to determine the importance of marketing educational services in improving the image of schools. The research method used in literature study. The data collection techniques in this study are by interviews, observations and document studies. The results of the study show that in managing educational institutions, it is very necessary to manage the marketing of educational services to sell school products so that they remain in demand by the community, with the hope of obtaining the largest number of students so that the existence of the school is recognized and can develop. It is important for schools to ensure the quality of services before marketing in order to attract the attention of the public as potential customers of education services.